”Foran loven”: moderne skandinavisk kortprosa over for Franz Kafkas roman "Processen" - Zańko, Aldona (Folia Scandinavica Posnaniensia, 2016)
The novel The trial, telling the story of the groundless arrest and prosecution of the bank clerk Josef K., remains one of the best-known and most influential works written by Franz Kafka. Depicting the pointless struggle of a man placed at the mercy of a remote, inaccessible authority, it gives a symbolic account of the human condition in the modern era, characterised by the lack of universal truth, estrangement, confusion and existential impotence. Grasping the very idea of existential modernity, the novel provides ongoing inspiration for a great number of modernist and postmodernist writers all over the world, including Scandinavia. In the article presented below, The trial is examined as an intertext within the genre of the Scandinavian short prose, as it unfolds at breakthrough of modernism and postmodernism. Starting with the literary and critical works of the Danish modernist Villy Sørensen, and moving forward throughout the Danish and Norwegian minimalism of the 1990's, the paper discusses a range of different aspects of The trial, as they reappear in the short stories written by some of the main representatives of the Scandinavian short story. In this way, the article elucidates the relevance of Kafka's novel as an intertext for contemporary Scandinavian short fiction, as well as draws attention to the dialogical dimension of the genre.